Correlation of Venous Blood Sugar Measured by Lab Method and Capillary Blood Sugar Measured by Glucometer in Neurosurgical Patients Receiving Dexamethasone - Sharma, Jyoti; Bala, Renu; Singh, Seema (Asian Journal of Neurosurgery, 2023)
Background Brain is vulnerable to extreme blood glucose levels that may occur due to multiple factors in neurosurgical patients; perioperative use of dexamethasone is the most common. Thus, frequent monitoring of blood sugar levels is advocated. This study aimed to assess correlation between venous blood sugar measured by lab method and capillary blood sugar by glucometer at various time intervals.Materials and Methods This prospective and observational study was conducted in 20 adult patients of either sex, American Society of Anesthesiologists grade I to III, scheduled to undergo brain tumor resection. The patients who were already on dexamethasone and received intraoperatively 8 mg dexamethasone were enrolled. Standard anesthesia technique and intraoperative monitoring were followed in all patients. Venous sample was withdrawn and blood sugar analyzed in laboratory, while at the same time capillary blood sugar was tested by glucometer. The sampling was done at baseline, 1 hourly after dexamethasone administration till 4 hours and then 8, 12, and 24 hours. The correlation between the two values was assessed.Results During the study, 160 venous and 160 capillary blood sugar levels were analyzed. Though capillary blood sugar levels were slightly higher than venous sugar levels, there was strong correlation between the two (Pearson correlation coefficient) with p-value less than 0.05 except at 24 hours when two values were not correlated.Conclusion Capillary blood sugar levels by glucometer have good correlation with venous sugar levels; therefore, this method may be adopted routinely for frequent blood sugar estimation as it is reliable, easy, and practical.
Keywords: neurosurgical; dexamethasone; blood glucose; capillary; venous